Kecemasan Mahasiswa terhadap Covid-19 Varian Baru Omicron - Lulukaningsih, Zuyina (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
The condition of the Covid-19 pandemic continued until the emergence of the Omicron variant, which can cause anxiety for students who practice at the hospital, because in the hospital there are several patients infected with Covid-19 who must be treated. This fact was also experienced by students of the Physiotherapy Study Program, Faculty of Psychology and Health, Widya Dharma Klaten University, who had to carry out comprehensive clinical practice at Bagas Waras Hospital during the Covid-19 pandemic. This type of research was a qualitative study with a phenomenological approach. The data collection technique used an instrument in the form of a questionnaire. To guarantee data validity, triangulation of data sources was used. Data analysis techniques using interactive descriptive and qualitative analysis flow models. The results of the study concluded that there were students who experienced mild anxiety when carrying out comprehensive clinical practice at Bagas Waras Hospital during the Covid-19 pandemic, because they felt worried, their thoughts made them anxious, the worst could possibly happen, and they were too worried that they often missed things that going on around it.Keywords: anxiety; the Covid-19 pandemic; omicron; studentABSTRAK Kondisi pandemi Covid-19 yang terus berlanjut hingga munculnya varian Omicron, yang dapat menyebabkan kecemasan bagi para mahasiswa yang melakukan praktik di rumah sakit, karena di rumah sakit ada beberapa pasien yang terinfeksi Covid-19 yang harus dirawat. Kenyataan ini juga dialami oleh para mahsiswa Program Studi Fisioterapi, Fakultas Psikologi dan Kesehatan, Universitas Widya Dharma Klaten, yang  harus melakukan praktik klinik komprehensif di RSUD Bagas Waras selama pandemi Covid-19. Jenis penelitian adalah studi kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data menggunakan instrumen berupa kuesioner. Untuk menjamin validitas data digunakan trianggulasi sumber data. Teknik analisis data menggunakan analisis deskriptif dan kualitatif interaktif model mengalir. Hasil penelitian menyimpulkan bahwa ada mahasiswa yang mengalami kecemasan ringan saat melakukan praktik klinik komprehensif di RSUD Bagas Waras selama pandemi Covid-19, karena merasa khawatir, pikiran membuat dirinya cemas, kemungkinan terburuk bisa saja terjadi, dan terlalu khawatir sehingga sering melewatkan hal-hal yang terjadi di sekitarnya.Kata kunci: kecemasan; pandemi Covid-19; omicron; mahasiswa